A comparative study of the performance of ISO and non ISO certified higher educational institutions, 1999-2004 - Taganguin, Lydia S. Lacanilao (2006)
The study compared the profiles of ISO and non-ISO certified Higher Educational Institutions (HEIs) in terms of PRC ratings, research output, and extension services. Data were gathered using the "ex post facto" descriptive research method and the techniques of documentary analysis. It combined quatitative and qualitative techniques designed to gather information about the present condition of HEIs. It was concluded that ISO-certified and non-ISO certified HEIs do not have significant differences in PRC ratings, research output, and Extension services. Numerous effects of ISO certifications on the management of HEIs were also enumerated.
Vita.
Thesis (Ph. D. Educational Administration)--University of the Philippines, Diliman.
Keywords: Education, Higher -- Standards -- Philippines -- National Capital Region; ISO 9000 Series Standards